ATAQLÍ DÁSTANSHÍ, BAXSHÍ FAZÍL YULDASH ULÍ HÁM OL ATQARǴAN «ALPOMISH» DÁSTANÍ HAQQÍNDA - Turdımuratova, A.B. (SCIENCE and SOCIETY, 2024)
The article discusses the Bulyngur school of storytellers and its famous representatives, who have a special role in Uzbek epic studies, the biography and repertoire of bakhshi Fazil Yuldash uly, a famous narrator of heroic dastans, the last representative of the Bulungur school, the performance of the «Alpomish» dastan and recording, publication, as well as the conclusions of scientists on fulfillment of dastan.